A comprehensive review of multi-level inverters, modulation, and control for grid-interfaced solar PV systems - Bhupender Sharma; Saibal Manna; Vivek Saxena; Praveen Kumar Raghuvanshi; Mohammed H. Alsharif; Mun-Kyeom Kim (Scientific Reports)
Abstract With the significant development in photovoltaic (PV) systems, focus has been placed on inexpensive, efficient, and innovative power converter solutions, leading to a high diversity within power converters and new system configurations for grid-connected PV (GCPV) systems. During the last decade, multilevel inverter (MLI) designs have gained popularity in GCPV applications. This article provides a wide-ranging investigation of the common MLI topology in contrast to other existing MLI topologies for PV applications. Furthermore, the various modulation techniques used in MLI switching are elucidated and contrasted. The modulation strategies are reviewed with particular regard to their comparative suitability for the modulation of MLIs for PV applications. This article also provides a comparative analysis of available MLI control techniques and controllers for GCPV applications in recent times.